If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9b + -7 + 3b = 15 Reorder the terms: -7 + -9b + 3b = 15 Combine like terms: -9b + 3b = -6b -7 + -6b = 15 Solving -7 + -6b = 15 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -6b = 15 + 7 Combine like terms: -7 + 7 = 0 0 + -6b = 15 + 7 -6b = 15 + 7 Combine like terms: 15 + 7 = 22 -6b = 22 Divide each side by '-6'. b = -3.666666667 Simplifying b = -3.666666667
| -6(3-x)=-18 | | 9(y-9)/2=-3y | | 7x-28-20=2x+2-5 | | (+76)-(-7)= | | B/4=15.5 | | 150+77x=240+54x | | -9b-7+3b=11 | | -2b=58 | | 134=-4x-2(4x-7) | | -6x+8=-2+2 | | -5/7+1/3 | | 5.6/0.4-r=8 | | 3x-1=3(x-1) | | 5t=6t+7 | | 599-5(21+20)=y | | 5(x+2)-3=12 | | 455=180+3x+1.5x | | 14+8x=-x-5 | | 4x^3-10x^2-64x+160=0 | | -3x+2x=5 | | -6=X+39/-9 | | 6x^2+5x=o | | 2-6(6+2k)=-106 | | -5r-(42+14r)=-99 | | 4x^3-10x^2-64+160=0 | | 163=-7x+3(7x+17) | | 9/3*3+7-3=y | | 3.5p=39.5 | | 2(4x+1)=4x-6 | | 8x-11=13+8u | | 3(x+2)-3x=12 | | 83=-5x+3(-3x-5) |